A Prospective, Phase 1 Trial of Nivolumab, Ipilimumab, and Radiotherapy in Patients with Advanced Melanoma - Postow, Michael A; Knox, Susan J; Goldman, Debra A; Elhanati, Yuval; Mavinkurve, Vikram; Wong, Phillip; Halpenny, Darragh; Reddy, Sunil K; Vado, Kenya; McCabe, Danielle; Ramirez, Kristen Aufiero; Macri, Mary; et al. (Clinical cancer research, 2020)
Preclinical data suggest that radiotherapy (RT) is beneficial in combination with immune checkpoint blockade. Clinical trials have explored RT with single-agent immune checkpoint blockade, but no trials have reported RT with the combination of nivolumab and ipilimumab. We conducted a phase 1 study of patients with stage IV melanoma receiving nivolumab and ipilimumab with two different dose-fractionation schemes of RT. Patients had at least one melanoma metastasis that would benefit from palliative RT and one metastasis that would not be irradiated. Nivolumab 1 mg/kg + ipilimumab 3 mg/kg and extracranial RT with a dose of 30 Gy in 10 fractions was administered in Cohort A, and then 27 Gy in 3 fractions was administered in Cohort B. The primary outcome was safety. Twenty patients were treated (10 in each cohort). The rates of treatment-related grade 3-4 adverse events in Cohort A and B were 40% and 30%, respectively. There were no grade ≥3 adverse events attributed to RT. Patients responded to treatment outside of the irradiated volume (Cohort A 5/10; Cohort B 1/9). No evaluable patients had progression of irradiated metastases. Immunologic changes were seen in the peripheral blood with increases in T-cell receptor diversity in some responding patients. RT with nivolumab and ipilimumab was safe compared with historical data of nivolumab and ipilimumab alone. Immunologic effects were observed in the peripheral blood. Randomized studies are ongoing to assess whether RT increases the efficacy of nivolumab and ipilimumab.